The role of organic cation transporter 2 inhibitor cimetidine, experimental diabetes mellitus and metformin on gabapentin pharmacokinetics in rats - Lima Benzi, Jhohann Richard de; Yamamoto, Priscila Akemi [UNESP]; Stevens, Jessica Hanna [UNESP]; Baviera, Amanda Martins [UNESP]; Moraes, Natalia Valadares de [UNESP] (Elsevier B.V., 2018)
Purpose: We investigated the influence of diabetes mellitus (DM), glycemic control with insulin, cimetidine (Oct2 inhibitor) and metformin (Oct2 substrate) on the kinetic disposition of GAB in rats. Main methods: Male Wistar rats were divided in five groups and all animals received an oral dose of 50 mg/kg GAB: (vehicle + GAB), cimetidine + GAB (single dose of cimetidine [100 mg/kg] intraperitoneally 1 h before GAB), metformin + GAB (single dose of metformin 100 mg/kg by gavage concomitantly with GAB), DM + GAB (single dose of 40 mg/kg streptozotocin (STZ) intravenously) and DM + GAB + insulin (single dose 40 mg/kg STZ intravenously and 2 IU insulin twice daily for 15 days). Pharmacokinetic analysis was based on plasma and urine data concentrations. Key findings: No differences in pharmacokinetic parameters were observed between vehicle + GAB x cimetidine + GAB and vehicle + GAB x metformin + GAB groups. Diabetes increased the fraction of GAB excreted unchanged in urine (vehicle+GAB: 0.48 [0.38-0.58]; DM + GAB: 0.83 [0.62-1.04]; DM + GAB + insulin: 0.88 [0.77-0.93]) (mean [95% confidence interval]) without any changes in GAB exposure. Insulin treated diabetic animals showed higher renal clearance compared to control (vehicle + GAB: 0.25 [0.18-0.30] L/h.kg; DM + GAB + insulin: 0.55 [0.45-1.43] L/h.kg), which was attributed to the diabetes-induced glomerular hyperfiltration.
Keywords: Oct2; Pharmacokinetics; Gabapentin; Diabetes mellitus